Effects of subnanometer silver clusters on the AgBr(110) photocatalyst surface: a theoretical investigation1. Issue 10 (21st October 2015) - Chi, Yuhua; Zhao, Lianming; Lu, Xiaoqing; An, Changhua; Guo, Wenyue; Liu, Yunqi; Wu, Chi-Man Lawrence
<x xml:space="preserve">Abstract</x> The geometrical and electronic structures and photocatalytic performance of subnanometer Agn clusters (n = 2–6) deposited on AgBr(110) are studied under the framework of density functional theory (DFT) plus Hubbard U contributions.